Educational Functions of Augmented Reality - Tomáš Jeřábek; Vladimír Rambousek (Charles University, 2018)
The theoretical study presented in this paper focuses on the use of augmented reality systems in education. It analyses the specifi c characteristics of augmented reality and, in the context of these parameters, it formulates didactic specifi cs of augmented reality given by the complex of didactically relevant parameters of the didactic means that distinguish it from other devices in terms of supporting the accomplishment of educational intentions. Th e paper also defi nes educational intentions of using augmented reality for increasing the informational value, exposition of temporally and spatially disparate processes and phenomena, simulations of phenomena, events and processes, acquisition and building of competence in specifi c situations and instructing in activities. Following the educational intentions, the paper also proposes complex organisational criteria for the use of augmented reality applications, which include, in particular, the proposed location for the implementation of augmented reality, the number of students for whom augmented reality is intended, the anticipated role of a student in augmented reality, required mobility and required parameters of content presentation.